Data on aquatic insects of Ngoc Linh Special-use Forest, Quang Nam province - Ngo Xuan, Nam (VNU Journal of Science: Natural Sciences and Technology, 2017)
Three investigations into species composition in aquatic insects in Ngoc Linh Special-use Forest in Quang Nam (March, September, 2015 and March, 2016). At 15 sampling sites in selected waterbodies, aquatic insects were sampled quantitatively by Surber net and qualitatively by hand net. The study has showed a total of 86 species, belonging to 69 genera, 40 families, 8 orders of aquatic insects: 24 Odonata species, 21 Ephemeroptera species, 13 Tricoptera species, 11 Hemiptera species, 7 Plecoptera species, 6 Coleoptera species, 3 Diptera spieces and 1 Megaloptera species. The three orders, Odonata, Ephemeroptera, Tricoptera, predominated (67,45%) the aquatic insect fauna in terms of species richness. This study has provided the data of aquatic insects in this area